A dataset for the automatic assessment of functional senior fitness tests using kinect and physiological sensors - Bernardino, Alexandre (2018)
This work presents a dataset of functional fitness tests acquired with Kinect v2 and physiological sensors. The dataset contains both young and senior subjects executing a number of fitness tests meeting scientific standards of reliability and validity. The main objective is the ability to assess lower body strength, endurance, gait speed, agility and balance from the data obtained from commercially accessible devices. The dataset can be used to develop algorithms to automate the assessment of fitness levels in low-cost computer based systems for use at home, gymnasiums or care centers.